ANALISIS PASAR MENGENAI KEHALALAN DAN ISU BOIKOT PRODUK KOSMETIK TERHADAP KEPUTUSAN PEMBELIAN - Aprilia Rahmasari; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research examines the impact of halal factors and boycott issues on cosmetic purchasing decisions in Indonesia. This research applies the library research method in collecting and reviewing library materials related to this research topic in order to find out how halal issues and boycotts influence consumer purchasing behavior. The research results prove that halal products have an important impact in determining purchasing decisions, and the boycott issue is proven to be influenced by the level of social awareness and the values ​​held by some consumers. These results provide information for cosmetic manufacturers to develop marketing strategies that are more effective and responsive to consumer preferences.